Internal and external factors affecting new product development performance - Vanya Cendana; Anton Wachidin Widjaja (President University, 2022)
The Covid-19 pandemic is strengthening the power of digital disruption. Over the decades, there has been a lot of research focusing on the factors affecting performance of new product development (NPD). However, there are gaps and conflicting results regarding factors affecting new product development performance. This study aims to determine the effect of network externalities and company's strategic orientation mediated by dynamic marketing capability and network capability in Indonesia. Data collection is carried out by simple random sampling, with the population of operational and managerial levels engaged in new product development processes in various firms. 61 Respondents mostly come from Electronic and Fast-Moving Consumer Goods industry, as for the year of work are equally distributed from 2 to above 10 years. The data obtained is processed using the Partial Least Square Structural Equation Modelling (PLS-SEM) method. This method allows us getting measurement and structural model where we test the t-value of each relationship. The result shows a new perspective on Dynamic Marketing Capability and Network Capability. It also shows the need for balancing dimensions of Strategic Orientation. Lastly, Network Externalities is proven to influence the performance of New Product Development.